“Diseño de un sistema experimental para la validación de simulaciones en redes tipo malla con flujo de agua”. - Carrillo López, Kevin Alexander (2022)
This project focuses on the design of an experimental module for the validation of simulations in mesh type networks and to determine the low precision in the calculation process caused by the lack of knowledge in the handling of the "Epanet" software, high costs in the pressure sensors and interactive calculation process in the validation. The experimental method was used in which measurement sensors for flow and pressure were installed, in addition to programming for data reception for subsequent processing and visualization, by the systemic method due to the lack of knowledge in the study and analysis of the mesh type networks it was essential to resort to the "Epanet" software from which instantaneous values of pressures and flows were obtained according to the defined parameters. A statistical method is determined to determine the percentage of error that exists when comparing the systemic method with the experimental one. The margin of error obtained between the calculations made by the two methods involved results in an error of 3.88 % for the first case analyzed, 4.57 % error for the second case, 4.88 % error for the third case and 6.07 % error between the two methods for the last case. It is considered that this is between the parameter established in the NFPA (National Fire Protection Association) that this error cannot exceed 15%, if a system exceeds this value it does not satisfy the needs and conditions under which it was designed.